Tom Clancy's Op center : Line of control - Clancy, Tom.; Rovin, Jeff.; Pieczenik, Steve R. (London : Harper Collins, 2001)
The eighth volume in the fast-selling series of high-tech, high-action thrillers centred on Washington's National Crisis Management Centre.
Keywords: Crisis management in government -- Fiction. -- United States; v; Adventure and adventurers -- Fiction